2018
DOI: 10.1002/imhj.21734
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Models of Infant Emotions and Needs Among the Gamo People of Southern Ethiopia

Abstract: How mothers perceive their infants' emotions and their subsequent responses are influenced by cultural values and beliefs. Mothers who live in particularly harsh environments may have perceptions about their infants' emotions that reflect not only cultural values but also constraints of the environment. In this qualitative study, 29 Gamo mothers living in rural Ethiopia were interviewed about perceptions of their infants' emotions, how they felt about these emotions, and what they believed their infants needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…We described the emotional tone surrounding instances of joint engagement to identify one way that joint engagement might be socialized, that is through the broad mechanisms of social rewards (e.g., to increase behavior with positive emotional tone) and social punishment (e.g., to decrease behavior with negative emotional tone). Although the literature supports the view that infant emotional expressivity differs across cultures (e.g., Bader & Fouts, 2018; Gaskins et al, 2017; Keller, 2019b; Otto, 2014), previous studies have not identified emotional tone surrounding joint attention across diverse socio‐ecological contexts. Western, middle‐class partners, of both human and chimpanzee infants, showed overwhelmingly positive emotional tone (Adamson & Bakeman, 1985), although levels of positive emotional tone were generally high in all human and chimpanzee groups.…”
Section: Species Comparisons Of Joint Engagementmentioning
confidence: 83%
See 1 more Smart Citation
“…We described the emotional tone surrounding instances of joint engagement to identify one way that joint engagement might be socialized, that is through the broad mechanisms of social rewards (e.g., to increase behavior with positive emotional tone) and social punishment (e.g., to decrease behavior with negative emotional tone). Although the literature supports the view that infant emotional expressivity differs across cultures (e.g., Bader & Fouts, 2018; Gaskins et al, 2017; Keller, 2019b; Otto, 2014), previous studies have not identified emotional tone surrounding joint attention across diverse socio‐ecological contexts. Western, middle‐class partners, of both human and chimpanzee infants, showed overwhelmingly positive emotional tone (Adamson & Bakeman, 1985), although levels of positive emotional tone were generally high in all human and chimpanzee groups.…”
Section: Species Comparisons Of Joint Engagementmentioning
confidence: 83%
“…With distal caregiving, caregivers tend to nurture high arousal and positive emotions (e.g., smiling and laughter, see Tronick et al, 1979). With proximal caregiving, caregivers may focus instead on the elimination of negative emotions (e.g., crying, see Demuth et al, 2012; Keller, 2018), on maintaining low arousal in infants (Dixon et al, 1981; Karasik et al, 2018), or on nurturing relatively neutral expressiveness in infants (Bader & Fouts, 2018; LeVine, 2007; Otto & Keller, 2015; Richman et al, 1992).…”
Section: The Process Of Decolonizing Joint Attentionmentioning
confidence: 99%
“…Parenting values are shaped by shared cultural beliefs or foundational schemata within societies [61]. Foundational schemata such as egalitarianism, autonomy, and independence [61] can shape parenting values and practices and have been found to be associated with breastfeeding [16,32], weaning [62,63], and responses to infants' emotions [21]. For example, Fouts and colleagues [16] argued that Bofi and Aka forager (Central African Republic) children's control over breastfeeding, including how often they fed, was related to the Aka's core cultural vale of personal autonomy.…”
Section: Parenting Values and Beliefsmentioning
confidence: 99%
“…The physical and social settings of the environment can affect where children sleep [ 18 ], who children play with [ 19 ], and what activities children engage in (e.g., household work) [ 20 ]. Parenting beliefs can include how mothers interpret and respond to their infants’ emotions [ 21 ]. The developmental niche of young refugee children may be altered as a result of the migration process.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted regarding the stoicism of the Ethiopian culture as well as the reluctance to show negative emotions, which may be a reason for lack of consistent discussion about emotions that may indicate mental illness (Neuner et al, 2012;Ayers et al, 2017;Evason, 2018). For example, a study conducted among mothers in Southern Ethiopia showed that their perception of infant emotions like fussing and crying were the result of physical illness as opposed to emotional upset (Bader and Fouts, 2018). Moreover, in the Southwest region of Ethiopia residents were likely to "deny those with mental illness their individual rights, prevent them from taking on various responsibilities and forbid people from marrying and living together" with those affected (Baumgartner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%